2005
DOI: 10.1080/09513590500097952
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor in the plasma, follicular fluid and granulosa cells of women with endometriosis submitted toin vitrofertilization – a pilot study

Abstract: Vascular endothelial growth factor (VEGF), a potent angiogenic factor that is altered in endometriosis, supports the immunological mechanism involved in this disease. The aim of the present study was to assess VEGF concentration in the plasma, follicular fluid (FF) and culture medium (CM) of granulosa cells from patients with endometriosis submitted to in vitro fertilization (IVF). A case-control study was conducted on 14 patients with endometriosis and 14 women without endometriosis submitted to IVF. Peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 34 publications
0
4
2
2
Order By: Relevance
“…In contrast, other authors have shown a significant increase in circulating levels of VEGF among women with endometriosis [38][39][40]. In our study, we found no significant modulation of VEGFA mRNA levels in the peripheral blood of patients with endometriosis compared to controls.…”
Section: Vascular Endothelial Growth Factorcontrasting
confidence: 84%
“…In contrast, other authors have shown a significant increase in circulating levels of VEGF among women with endometriosis [38][39][40]. In our study, we found no significant modulation of VEGFA mRNA levels in the peripheral blood of patients with endometriosis compared to controls.…”
Section: Vascular Endothelial Growth Factorcontrasting
confidence: 84%
“…Some studies have actually reported no significant difference in VEGF serum levels in patients with endometriosis compared with controls [24,25]. In contrast, other authors have shown a significant increase in circulating levels of VEGF among women with endometriosis [20,21,22,23]. In our study, we found no significant modulation of VEGFA mRNA levels in the peripheral blood of patients with endometriosis compared to controls.…”
Section: Discussioncontrasting
confidence: 51%
“…Previous studies have indicated a significant increase in VEGF and its mRNA expression in endometriotic lesions compared to controls or eutopic endometrium [15,16,17,18,19]. Contradictory results have been reported concerning peripheral blood levels of VEGF in women with or without endometriosis; some published data reported higher levels in cases of endometriosis [20,21,22,23], while other data reported no differences at all [24,25]. …”
Section: Introductionmentioning
confidence: 53%
“…In contrast, the evidence for up-regulation of inflammatory and angiogenic markers on a systemic level is mixed. The angiogenic markers VEGF, leptin and/or glycodelin are increased in women with endometriosis (9, 45-47) or do not change (18, 48-54). Similarly, 2 of the 3 inflammatory markers assayed in this study, MCP-1 and MIF have had mixed results in past studies with some reporting elevated blood levels in women with endometriosis (55-57) and others showing no difference (52, 58, 59).…”
Section: Discussionmentioning
confidence: 99%